Imaging Borrelly - Soderblom, L.A.; Boice, D.C.; Britt, D.T.; Brown, R.H.; Buratti, B.J.; Kirk, R.L.; Lee, M.; Nelson, R.M.; Oberst, J.; Sandel, B.R.; Stern, S.A.; Thomas, N. (Icarus, 2004)
The nucleus, coma, and dust jets of short-period Comet 19P/Borrelly were imaged from the Deep Space 1 spacecraft during its close flyby in September 2001. A prominent jet dominated the near-nucleus coma and emanated roughly normal to the long axis of nucleus from a broad central cavity. We show it to have remained fixed in position for more than 34 hr, much longer than the 26-hr rotation period. This confirms earlier suggestions that it is co-aligned with the rotation axis. From a combination of fitting the nucleus light curve from approach images and the nucleus' orientation from stereo images at encounter, we conclude that the sense of rotation is right-handed around the main jet vector. The inferred rotation pole is approximately perpendicular to the long axis of the nucleus, consistent with a simple rotational state. Lacking an existing IAU comet-specific convention but applying a convention provisionally adopted for asteroids, we label this the north pole. This places the sub-solar latitude at ~60° N at the time of the perihelion with the north pole in constant sunlight and thus receiving maximum average insolation.